(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A new Zn(II) complex with the monodentate ligand 3-fluoroaniline, ZnCl2(C6H4FNH2)2, has been prepared and characterized by single crystal X-ray diffraction, Solid state NMR, IR and UV-visible spectroscopies. The Zn(II) ion, located on a special position, is tetracoordinated by two nitrogen atoms of two 3-fluoroaniline monodentate ligands and two chlorine ligands. In the atomic arrangement, the ZnCl2(NH2)2 entities are interconnected via N-H…Cl hydrogen bonds to form inorganic layers parallel to the (b, c) plane. The organic 3-fluorophenyl groups are located between these layers and connect each other via C-H…F hydrogen bonds to perform an infinite three-dimensional network. The F atom of the 3-fluoroaniline ligand is disordered over two positions. An F-F interaction between neighboring fluorine atoms contributes also to the structure cohesion. The 13C and 15N CP-MAS NMR spectra are in agreement with the X-ray structure. DFT calculations allow the attribution of the carbon peaks to the different independent atoms. Solid-state UV-Vis spectrum of the complex has been assigned to ligand and charge transfer transitions.